Il tempo disgiunto e la necessità della contingenza: dall'à-venir all'a-venir? - Habdankaitė, Daina (Filosofia, 2023)
This paper aims at rethinking Meillassoux’s idea of the necessity of contingency by putting it in the context of Derridian and Deleuzian attempts of reimagining the temporal triad of past, present, and future. The paper raises a problem of compatibility of two Meillassoux’s ontological assumptions: A) the real has no ground, that is, there is no principle of ontological causal necessity; B) something radically new can emerge in the real. A and B can be compatible if and only if the real in question has a structure which is both coherent enough to be torn by the ontological rupture and remains irreducible to causality-based principles. The author of this paper holds that structure of the real that is necessary to ground the compatibility of the two assumptions requires developing a notion of the future as what is to come yet never comes.